Synthesis and Characterization of the O‐Alkylation Products of Resorcinarene. Issue 8 (30th January 2013) - Salorinne, Kirsi; Nauha, Elisa; Nissinen, Maija; Ropponen, Jarmo
Abstract: O ‐Substitution reactions of tetramethoxyresorcinarene with alkyl halides produced a variety of partially O ‐alkylated resorcinarene derivatives with terminal alkyne functionality. The degree of alkylation was affected by the reactivity of the alkylating halide used. NMR spectroscopy proved to be an ideal tool for analyzing the complex reaction mixtures and the isolated products based on the symmetry and degree of alkylation of the resorcinarene derivatives. Single‐crystal X‐ray diffraction studies furthermore showed diversity in the self‐assembly of the various O ‐alkylation products that was greatly affected by the degree of alkylation, as well as the nature of the alkyne moiety. Abstract : A method for the preparation of partially O ‐alkylated resorcinarenes with terminal alkyne functionality is described. NMR spectroscopy was used as a convenient tool in the identification of a complex mixture of O ‐alkylation products formed in the reaction based on their structural symmetry.